Effects of gaseous sulphuric acid on diesel exhaust nanoparticle formation and characteristics - Rönkkö, Topi; Lähde, Tero; Heikkilä, Juha; Pirjola, Liisa; Bauschke, Ulrike; Arnold, Frank; Schlager, Hans; Rothe, Dieter; Yli-Ojanperä, Jaakko; Keskinen, Jorma (Environmental science & technology, 2013)
Diesel exhaust gaseous sulphuric acid (GSA) concentrations and particle size distributions, concentrations, and volatility were studied at four driving conditions with a heavy duty diesel engine equipped with oxidative exhaust after-treatment. Low sulfur fuel and lubricant oil were used in the study. The concentration of the exhaust GSA was observed to vary depending on the engine driving history and load. The GSA affected the volatile particle fraction at high engine loads; higher GSA mole fraction was followed by an increase in volatile nucleation particle concentration and size as well as increase of size of particles possessing nonvolatile core. The GSA did not affect the number of nonvolatile particles. At low and medium loads, the exhaust GSA concentration was low and any GSA driven changes in particle population were not observed. Results show that during the exhaust cooling and dilution processes, besides critical in volatile nucleation particle formation, GSA can change the characteristics of all nucleation mode particles. Results show the dual nature of the nucleation mode particles so that the nucleation mode can include simultaneously volatile and nonvolatile particles, and fulfill the previous results for the nucleation mode formation, especially related to the role of GSA in formation processes.